Assessing Obstetrician-Gynecologists Understanding of Their Role Under the Affordable Care Act [8M]. (May 2016) - Stamm, Carol A.; Topp, Daniel; Dwinnell, Brian G.; Blumhagen, Rachel; Gilroy, Christine
Abstract : INTRODUCTION: A survey was sent to Colorado Section of ACOG members with the objective of assessing understanding and compliance with preventive care aspects of the Affordable Care Act (ACA). Obstetrician gynecologists are potentially uniquely positioned to serve as specialists in women's health and primary care providers although they are not specifically designated as primary care providers. METHODS: A REDCap linked survey containing questions on screening for cervical cancer, sexually transmitted infections, breast cancer, contraception, pregnancy intention, domestic violence, depression, vaccination provision, utilization of electronic medical records, activity within ACOG, and basic anonymous demographics was emailed to members. RESULTS: Over a four month period, 87 responses from 668 email addresses were obtained, reflecting approximately 14.5% of Colorado members. 98.9% of respondents considered themselves specialists in women's health and 64.4% of respondents also considered themselves to be primary care providers for women. Overall, respondents self reported high compliance with ACA screening guidelines: 86% reported screening for depression, and 96% for screening appropriately for cervical cancer, but 60.9% of respondents self-reported referral of patients who need vaccinations. CONCLUSION: ACOG members responding to this survey reported high levels of compliance with most of the ACA recommendations for preventive care except vaccination, providing an area for expanded education or analysis for reimbursement and other barriers. Although they consider themselves primarily as specialist in women's health, more than half still see themselves as primary care providers, which may have reimbursement implications.